种用于智能家居的压力感应器、控制系统及其控制方法 (2018)
本发明涉及种智能家居设备，尤其是种用于智能家居的压力感应控制系统，包括：Z-WAVE压力处理模块、天线模块E、电源模块、电容式压力传感器S1、比较器U1、运算放大器U2。电容式压力传感器S1受压力时，比较器U1能够对比受压力的电信号、以及未受压力的基准信号，持续受力时，基准信号恢复为受压力的基准信号，比较器不输出信号，本发明的压力传感器能够识别出移动的人体以及放置在地板上的静止物品，更加智能化，调节灯光时更加的节能。而使用该压力传感器的压力感应器控制系统也更加的智能、节能。另外用于智能家居的压力感应器控制系统，本发明控制系统能够和智能家居的其他设备形成联动控制。 The invention relates to smart home furnishing, in particular to a pressure sensing control system used for smart home furnishing. The pressure sensing control system used for the smart home furnishing comprises a Z-WAVE pressure processing module, a wireless module E, a power supply module, a capacitance type pressure sensor S1, a comparator U1 and an operational amplifier U2. When the capacitance type pressure sensor S1 suffers pressure, the comparator U1 can compare electric signals under pressure with reference signals without pressure, when the capacitance type pressure sensor continuously suffers pressure, reference signals are restored into reference signals under pressure, and the comparator does not output signal. The pr